Intraspecific competition in larvae of the larger grain borer, Prostephanus truncatus (Horn) with maize grains - Vowotor, K.A.; Meikle, W.G.; Ayertey, J.N.; Borgemeister, C.; Markham, R.H. (Springer, 1998)
The effects of egg clutch size on development and survivorship of the larger grain borer, Prostephanus truncatus (Horn) (Col.: Bostrichidae) on maize were measured in the laboratory using single grains of the white maize variety, TZSR-W, at 30 ± 2°C and 70 ± 5% RH. Varying numbers of P. truncatus eggs (1, 2, 4, 8, or 16) were introduced into a hole drilled into a single maize grain. Destructive sampling was used at regular intervals to obtain data on immature developmental parameters, the location of immatures within the grain and the weight and sex of any emerged adults. First instars fed mainly on the floury endosperm tissue whereas the second and third instars preferred the germ tissue. Mortality due to competition was highest in first instars. At high initial densities (> 4 per kernel), some P. truncatus larvae reduced competition by moving out of the grain. A maximum of 6 adults emerged from a single grain. The mean number of adults that emerged per grain for initial egg densities of 8 and 16 were 3.3 and 3.5, respectively. Prostephanus truncatus adult weight at emergence was not significantly influenced by initial egg density except in the case of clutch size 16. The sex ratio of emerged adults was also unaffected by competition, and was always 1:1. Complete developmental period within grains ranged between 28 and 32 days.